Exome Sequencing Identifies Pathogenic and Modifier Mutations in a Child With Sporadic Dilated Cardiomyopathy. Issue 12 (December 2015) - Long, Pamela A.; Larsen, Brandon T.; Evans, Jared M.; Olson, Timothy M.
Abstract : Background: Idiopathic dilated cardiomyopathy (DCM) is typically diagnosed in adulthood, yet familial cases exhibit variable age‐dependent penetrance and a subset of patients develop sporadic DCM in childhood. We sought to discover the molecular basis of sporadic DCM in an 11‐year‐old female with severe heart failure necessitating cardiac transplantation. Methods and Results: Parental echocardiograms excluded asymptomatic DCM. Whole exome sequencing was performed on the family trio and filtered for rare, deleterious, recessive, and de novo variants. Of the 8 candidate genes identified, only 2 had a role in cardiac physiology. A de novo missense mutation in TNNT2 was identified, previously reported and functionally validated in familial DCM with markedly variable penetrance. Additionally, recessive compound heterozygous truncating mutations were identified in XIRP2, a member of the ancient Xin gene family, which governs intercalated disc (ICD) maturation. Histomorphological analysis of explanted heart tissue revealed misregistration, mislocalization, and shortening of ICDs, findings similar to Xirp2 −/− mice. Conclusions: The synergistic effects of TNNT2 and XIRP2 mutations, resulting in perturbed sarcomeric force generation and transmission, respectively, would account for an early‐onset heart failure phenotype. Whereas the importance of Xin proteins in cardiac development has been well established in animal models, this study implicates XIRP2 as a novel modifier gene in the pathogenesis of DCM.